The Single Candidate in the 2020 Regional Head Election is Viewed From the Perspective of Democratic Principles Adopted by the Indonesian State - Shintamy Nesyicha Syahril; Ahmad Redi (Journal of Social Research, 2023)
The development of Indonesia's governance is currently quite rapidly developing. Indonesia is one of the countries that adheres to a democratic system. This understanding is elaborated constitutionally and fundamentally in the Preamble to the NRI Constitution of 1945 Alenia IV, which affirms one of the country's policies which reads: "Peoplehood led by wisdom in consultation / representation". The purpose of this study is to determine the legal consequences of having a single candidate in the general election when viewed from the perspective of democratic principles in Indonesia. This study uses normative research, which uses secondary data in analyzing the problems raised and supported by primary legal materials consisting of laws and regulations, court decisions, legal theories and legal principles recognized by civilized nations (general theory recognized by civilized nations ), secondary legal materials such as journals, books, and other scholarly articles, and tertiary legal materials consisting of encyclopedias, and legal dictionaries. The legal framework for regional elections must be able to guarantee the holding of democratic elections. However, seeing the condition of a single candidate, it caused a reaction from elements of the community by submitting a judicial review to the Constitutional Court regarding the rules for nominating regional heads. As a result of this vacancy, it has an impact on postponing the regional elections until the next regional elections so that the regions that are postponed will be led by temporary officials appointed by the Ministry of Home Affairs. This circumstance was deemed by the plaintiff to be unfair to the spouse of a qualified candidate to run in the local election competition. The existence of a single candidate begins with a legal vacuum when the requirements for at least two pairs of candidates to be able to hold elections are not met, so that the legal vacuum results in the inability to hold regional elections.